Optimization of aluminum 6061 surface integrity on dry-running machining CNC milling using Taguchi methods - Rifky Maulana Yusron; Mohamad Imron Mustajib; Imam Hanafi (Journal of Energy, Mechanical, Material, and Manufacturing Engineering, 2023)
Aluminum 6061 is an aluminum alloy, which contains aluminum as main entails, then magnesium and silicon are mixed as alloying elements. It had a good capability for corrosion resistance, heat treatable, formed, and welded. Computerized Numerical Control had excellent capability to process mass-production products. Unsubstantial machining parameter setting will lead to a lack of surface roughness or even worse damage on tool steel. The aim of this research is to arrange data about surface integrity conducted by Dry-running machining CNC Milling. Surface integrity included surface roughness and micro-cracks. Aluminum 6061 is chosen as the material. The observed parameter machining in this research is cutting speed 3 is levels 60, 70, 80 mm/minute, then depth of cut is 3 levels 300, 380, 450 mm/minute and depth of cut is 3 levels 0.5, 0.75, 1.0mm. Taguchi L9 (33) was used as a design experiment to find optimum parameters. Based on the result of the experiment in this research, the optimum surface roughness founded on the machining parameter combination of cutting speed was 80 m/min, feed rate 300 mm/min, and depth of cut was 0.5 mm.